SINUSOIDAL ELECTROMAGNETIC FIELD DECREASES OSTEOGENIC DIFFERENTIATION OF RAT BONE MARROW MESENCHYMAL STEM CELLS - ALTEMEMY, DHIYA; GHASEM KASHANI, MARYAM HAJI; N. WENAS, OSAMAH (International Journal of Applied Pharmaceutics, 2024)
Objective: The widespread use of household electrical appliances generating electric and magnetic fields was a significant focus of WHO attention because of its serious threat to human health, especially osteogenesis. This research investigated the effect of 50 Hz frequency (1 mT intensity) sinusoidal EMF (SEMF) on the osteogenic differentiation of rat bone marrow stem cells (rBMSCs) in vitro. Methods: Experimental groups were: positive control (cells cultured in osteogenic medium supplemented with 7-10 M Dexamethasone, negative control (cells cultured in α-MEM/10% FBS, 10 mmol Beta-Glycerol-Phosphate, 15% FBS, 50 ug/ml Ascorbic Acid bi-Phosphate, 100 unit/ml Penicillin) and for the EMF group, cells exposed to SEMF (50 Hz, 1 mT, 30 min/day) for 14 and 21 d. Alizarin red staining, Alkaline phosphatase activity, and QRT-PCR were performed. Results: The EMF group exhibited weaker positive stains for ALP and Alizarin red than the positive control group. The Runx2 and Ocn gene expression levels were significantly decreased compared to negative control at 14 and 21 d of EMF exposure, respectively. After 14 and 21 d of exposure, Runx2 and Ocn gene expression were much lower in the EMF group than in the positive control group. Conclusion: SEMF (1 mT, 50 Hz, 30 min/day) could retarded osteogenesis and reduce the osteogenic differentiation of rBMSCs.